Kearifan Sunda, Kearifan Semesta: Menelusuri Jejak Islam dalam Khazanah Budaya Sunda - Agus Ahmad Safei (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Sundanese culture and Islam has been concluded by anthropologists as two inseparable things. Corelationship between Sundanese culture and Islam is like that of sugar and its sweetness which cannot be separated. Often stated that Islam and Sundanese culture bear similar paradigm. On the one side, Islam views and comprehends the world as expressions of absolute principles and recorded in divine revelation of God. On the other, Sundanese culture has long laid down absolute values that manifest on folkways and traditions. But, social acceptance of this is not without problem. The relation between Islam and Sunda must not be exagerated. We need to be proporsional in identifying similarities and differences of those two cultural entities.